Decline of Empathy after the First Internship: Towards a More Functional Empathy? - Givron, Hélène; Desseilles, Martin (Santé mentale au Québec)

(untitled) (Revue Santé mentale au Québec, 2020)
Research has shown a decline in empathy as medical studies progress. Among various hypotheses, an explanation track evoked is the first contact with the internship.Objectives This quasi-experimental study was designed to examine the impact of the first internship in medical students. Our research question was: “to what extent the first internship may decreased the empathy’s scores of our 3d year medical students?”Methods We measured the empathy of 220 third year medical students before and after their first internship (3 weeks) in family medicine. Using online surveys methodology, we collected data about empathy (“Interpersonal Reactivity Index”: IRI), epidemiology, professional orientation choices.Results Statistical analyses revealed a small but significant decrease in IRI’s “fantasy,” “empathic concern” and “personal distress” subscales.Conclusion These results suggest a potential impact of the first internship on empathic skills. The fact that the students’ score for the “personal distress” subscale (which characterizes a difficulty in managing their emotions) decreases is actually a rather good thing. These data raise the question of the “function” of this loss of empathy. The fact that this score decreases after first internship, may indicate a positive change for these medical students: towards better emotional regulation and more functional affective empathy.